Influence of growing conditions on morphological and anatomical characteristics of pine needles in the northern taiga - Olga N. Tyukavina; Nikolay A. Neverov; Denis N. Klevtsov (Journal of Forest Science, 2019)
The aim of the study was to determine the adaptive characteristics of pine needles associated with age and different growing conditions. The length of the needles decreases and its variability reduces with increasing dryness and poverty of the soil. In oppressed trees, the coefficient of variability of the length of the needles on the tree is 8%. The coefficient of variation in the length of needles approaching 20% will indicate the best conditions for the growth of a particular tree. Trends of the dependence of width and thickness of needles on growing conditions were not identified. The area of needles in pine forests with optimal water regime of soils (blueberry, cowberry type) varies in the range of 112-124 mm2. In extreme growing conditions pine needles area is reduced by 27-33% and equals 76-86 mm2. These ranges of values of the areas of needles are typical for plantings of the third and fourth classes of age. Changing the width and thickness of the needles is aimed at compensating for changes in the length of the needles in the direction of maintaining the optimal area for these conditions needles. In extreme conditions, the area of the assimilating tissue increases, and the area of the conducting tissue (stele) decreases. Correlation dependences of the area of the stele of needles with the cross-sectional area, with the area of conducting beams, with the number of resin canals and with the cover fabric are revealed.